SELF-REGULATED LEARNING DAN PENYESUAIAN DIRI DENGAN SOMATISASI PADA MAHASISWA TINGKAT AKHIR - Widya Puteri, Ika Apriati; Latifah, Nurul; Indah Muslimah, Alfiana (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2023)
This study aims to determine the relationship between selfregulated learning and adjustment to somatization in final year students at the Islamic University "45" Bekasi. This research uses quantitative. The subjects in this study were final year students at the Islamic University "45" Bekasi, totaling 88 students. This study uses a self- regulated learning scale with a Cronbach Alpha reliability value of 0.850, an adjustment scale with a Cronbach Alpha reliability value of 0.894, and a somatization scale with a Cronbach Alpha reliability value of 0.963. The data analysis technique used descriptive technique, assumption test (normality test and linearity test) and hypothesis test (Spearman Rho test and Simple Linear Regression). The results of this study indicate that there is a negative relationship between self- regulated learning and somatization, the correlation coefficient value is -0.267. And there is a negative relationship between self-adjustment and somatization, the correlation coefficient value is -0.254. While the results of a simple linear regression test between selfregulated learning have an influence on somatization, the coefficient of determination (R2) is 0.048. And self-adjustment has an effect on somatization, the coefficient of determination (R2) is 0.069